Development of video tutorials on building construction and utilities subjects assisted by Bandicam application for grade XI students at vocational high school - Hadi Suryono; Putu Sudira (JINoP (Jurnal Inovasi Pembelajaran), 2024)
The implementation of Building Construction and Utilities learning for class XI in Vocational High School (VHS) has faced several challenges including student understanding, teachers’ competency, and learning media. This study aims to result in a product, including the feasibility test and effectiveness on the topic of door and window frame details drawing assisted by the Bandicam application. We employed the Research and Development (R&D) model of 4D Thiagarajan. The trial was conducted on 14 students of the Building Information and Modeling Design (DPIB) expertise program class XI with input from 2 experts and 1 teacher. The data was collected through interviews, observations, and questionnaires. The obtained data was analysed using quantitative and qualitative descriptive analysis and descriptive statistics. The results show that the 4 video products were feasible and effective as seen from the improvement of student learning outcomes in the subject of building construction and utilities.